End-trajectory sliding mode control algorithm design of hybrid polishing robot based on nonlinear disturbance observer - Sun, Bo (Strojniški vestnik, 2026)
The five-degrees-of-freedom (5-DOF) hybrid polishing robot is utilized for machining large optical mirrors. Since the existing kinematics control strategy does not meet high-precision control requirements, it is necessary to develop a dynamics controller to improve the operational performance of the robot. To enhance the trajectory control accuracy of the polishing robot’s end-effector, a sliding mode control algorithm based on a nonlinear disturbance observer is proposed. First, the dynamic model, which accounts for joint friction effects, is derived using the Newton-Euler method, and a complete explicit dynamic model is established through parameter substitution. Subsequently, considering the influence of the coupling of inertia parameters of each component in the dynamic model on computational efficiency, the model is simplified while compensating for errors caused by neglected terms via the Whale Optimization Algorithm-Elman (WOA-Elman) algorithm to reconstruct the dynamic model with error compensation terms. Finally, based on an analysis of the reaching law and the design of the nonlinear disturbance observer, the end-effector trajectory sliding mode control algorithm is developed. Simulation and experimental results indicate that the inclusion of an improved reaching term effectively reduces system chattering. Furthermore, the nonlinear disturbance observer is employed to estimate system errors and external disturbances, significantly mitigating error fluctuations during the convergence process and thus validating the robustness and high precision of the trajectory tracking control system for the polishing robot.
Keywords: dinamični model; disturbance observer; drsni način krmiljenja; dynamical model; hibridni polirni roboti; hybrid polishing robots; krmiljenje sledenja trajektoriji; opazovalnik motenj; sliding mode control; trajectory tracking control